Plant-Derived Saponins: A Review of Their Surfactant Properties and Applications - Summi Rai; Eliza Acharya-Siwakoti; Ananda Kafle; Hari Prasad Devkota; Ajaya Bhattarai (Sci, 2021)
In response to increasing natural surfactant demand and environmental concerns, natural plant-based surfactants have been replacing synthetic ones. Saponins belong to a class of plant metabolites with surfactant properties that are widely distributed in nature. They are eco-friendly because of their natural origin and biodegradable. To date, many plant-based saponins have been investigated for their surface activity. An overview of saponins with a particular focus on their surface-active properties is presented in this article. For this purpose, works published in the past few decades, which report better surfactant relevant properties of saponins than synthetic ones, were extensively studied. The investigations on the potential surfactant application of saponins are also documented. Moreover, some biological activities of saponins such as antimicrobial activity, antidiabetic activity, adjuvant potentials, anticancer activity, and others are reported. Plants rich in saponins are widely distributed in nature, offering great potential for the replacement of toxic synthetic surfactants in a variety of modern commercial products and these saponins exhibit excellent surface and biological activities. New opportunities and challenges associated with the development of saponin-based commercial formulations in the future are also discussed in detail.